In vitro generation of endothelial microparticles and possible prothrombotic activity in patients with lupus anticoagulant - Combes, Valéry (American Society for Clinical Investigation, 1999)
Microparticles (MPs) resulting from vesiculation of platelets and other blood cells have been extensively documented in vitro and have been found in increased numbers in several vascular diseases, but little is known about MPs of endothelial origin. The aim of this study was to analyze morphological, immunological, and functional characteristics of MPs derived from human umbilical vein endothelial cells (HUVECs) stimulated by TNF, and to investigate whether these MPs are detectable in healthy individuals and in patients with a prothrombotic coagulation abnormality. Electron microscopy evidenced bleb formation on the membrane of TNF-stimulated HUVECs, leading to increased numbers of MPs released in the supernatant. These endothelial microparticles (EMPs) expressed the same antigenic determinants as the corresponding cell surface, both in resting and activated conditions. MPs derived from TNF-stimulated cells induced coagulation in vitro, via a tissue factor/factor VII–dependent pathway. The expression of E-selectin, ICAM-1, αvβ3, and PECAM-1 suggests that MPs have an adhesion potential in addition to their procoagulant activity. In patients, labeling with αvβ3 was selected to discriminate EMPs from those of other origins. We provide evidence that endothelial-derived MPs are detectable in normal human blood and are increased in patients with a coagulation abnormality characterized by the presence of lupus anticoagulant. Thus, MPs can be induced by TNF in vitro, and may participate in vivo in the dissemination of proadhesive and procoagulant activities in thrombotic disorders.